The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/cb.1754
|View full text |Cite
|
Sign up to set email alerts
|

Claiming best or better? The effect of target brand's and competitor's puffery on holistic and analytic thinkers

Abstract: Previous empirical studies have yielded contradictory results about how consumers react to puffed claims in advertisements. This study addresses this issue by considering how consumers' thinking style and competitors' puffery interact to influence consumers' brand attitude in terms of product puffery. Drawing upon experiments using fictitious and real brand names, three studies provide converging evidence that holistic thinkers will form a more positive brand attitude when exposed to the target brand's low‐puf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Studies applying the factor of analytic-holistic cognitive styles to advertising have found that an explanation for the differences in perception of and responses to food advertising can be offered by accounting for the cognitive tendencies of consumers [108]. Holistic thinkers were more sensitive to food advertising claims made by the researchers and their opinions of the food products were more variable depending on the type of advertisement shown.…”
Section: Multi-module Stimulimentioning
confidence: 99%
“…Studies applying the factor of analytic-holistic cognitive styles to advertising have found that an explanation for the differences in perception of and responses to food advertising can be offered by accounting for the cognitive tendencies of consumers [108]. Holistic thinkers were more sensitive to food advertising claims made by the researchers and their opinions of the food products were more variable depending on the type of advertisement shown.…”
Section: Multi-module Stimulimentioning
confidence: 99%
“…A few recent studies have identified how analytic and holistic differences can induce divergent responses between individual consumers in applied settings of food perception (Vanbergen, Irmak, & Sevilla, 2020; Yang, Xie, & Su, 2019). Hildebrand, Harding, and Hadi (2019) contributed to this developing body of interest by displaying how holistic consumers are significantly more impacted than analytic consumers by food advertisement contextual cues, which can be specifically impactful during the shopping piece of food behaviors from advertisements influencing shopping decisions (Haider & Shakib, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, however, a surprising omission from structural alignment research is the role of consumer characteristics (i.e., motivation and individual difference) in processing different types of product attributes (for exceptions, see Lee & Lee, 2016; Malkoc et al, 2005; Nam et al, 2009). In previous studies on the moderating effect of consumer characteristics and individual differences on information processing, it is revealed that psychological factors such as need for cognition and analytic versus holistic thinking style are important in determining advertising effectiveness (Kulkarni et al, 2020; Yang et al, 2019). In addition, Kalro et al (2013) assert that consumers are not always affected by comparative advertising strategies, which they argue is due to differences in how individuals process information.…”
Section: Theoretical Backgroundmentioning
confidence: 99%